RAPID DISCRIMINATION AMONG METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS ISOLATES USING VARIABLE NUMBER TANDEM REPEAT ANALYSIS IN A SAMPLE OF IRAQI PATIENTS AND - Abd Zaid, A. M.; Kandala, N. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
There is so little information available in Iraq about genetic variability in methicillin resistant Staphylococcus aureus (MRSA), so current study aimed to use six tandem repeat loci of multilocus variable number tandem repeat (MLVA) typing to discriminate among MRSA, so to achieve the aim of this study, six loci, clfA, clfB, sdrC, spa, sspa and sav1078 were selected for multiplex PCR. The PCR product were subjected to capillary electrophoresis by using ABI-Genetic analyzer, then the data were analyzed by using GeneMapper™ Software 5. Fragment sizes were converted into repeats number. The total number of repeats are used to generate allelic profile. The allelic profile used to draw the minimum spanning tree and dendrogram , all the 85 MRSA isolates are clustered into 54 MLVA type.